2006
DOI: 10.1186/1479-5876-4-33
|View full text |Cite
|
Sign up to set email alerts
|

Affordable flow cytometry for enumeration of absolute CD4+ T-lymphocytes to identify subtype C HIV-1 infected adults requiring antiretroviral therapy (ART) and monitoring response to ART in a resource-limited setting

Abstract: Background: The World Health Organization (WHO)'s "3 × 5 program" has spurred efforts to place 3 million people on combination antiretroviral therapy (ART) for treatment of AIDS in resource-limited countries. Paradoxically, the cost of CD4 + T-lymphocyte count essential for decision-making to commence HIV positive adults on ART as well as for monitoring responses to ART remains unaffordable in most resource-limited countries. Thus, low-cost methods for enumerating CD4 + T-lymphocyte are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 13 publications
3
32
0
6
Order By: Relevance
“…Previous studies that evaluated the first version of CyFlow Counter (CY-S-3021) or other CyFlow instruments (e.g. CyFlow Green, CyFlow Blue) showed similar results to this study [15], [17], [18], [29], [33], [35], [36], confirming the adequate performance of the newly available stabilized reagents on the most recent version of the CyFlow Counter (CY-S-3022). Only a few studies showed that CyFlow Counter and the CyFlow Green gave higher CD4 counts compared to the reference instruments [30], [37].…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies that evaluated the first version of CyFlow Counter (CY-S-3021) or other CyFlow instruments (e.g. CyFlow Green, CyFlow Blue) showed similar results to this study [15], [17], [18], [29], [33], [35], [36], confirming the adequate performance of the newly available stabilized reagents on the most recent version of the CyFlow Counter (CY-S-3022). Only a few studies showed that CyFlow Counter and the CyFlow Green gave higher CD4 counts compared to the reference instruments [30], [37].…”
Section: Discussionsupporting
confidence: 87%
“…The CD4 + T cell absolute count was performed using a Partec CyFlow ® Counter as described before (Zijenah et al, 2006; Fryland et al, 2006). …”
Section: Methodsmentioning
confidence: 99%
“…There is no need to lyse red blood cells and there are no wash steps. Absolute CD4 cell numbers determined using CyFlow have been compared with those obtained using FASCount in Zimbabwe, Uganda, Nigeria and Thailand [10][11][12][13]. In each case, there was a strong correlation between the results seen with these two systems with r values of 0.99, 0.86, 0.93 and 0.97, respectively.…”
Section: Flow Cytometric Cd4 Cell Analysismentioning
confidence: 92%